TOLERANSI BERAGAMA DALAM TAFSIR ULAMA JAWA: (Telaah Pemikiran KH. Misbah Musthofa dalam Tafsir Al-Iklil) - Hambari , Syaddad Ibnu (QOF, 2020)
The 2001 WTC bombing incident has made Islam called a terrorist religion and continues to stigmatize radicalism, even recently, it is anti-semitic. The embedding of stigmas has made many scholars try to bring back a paradigm that Islam is a tolerant religion and has universal compassion, even though some Islamic scholars later went too far in interpreting this tolerance, there was an understanding of religious equality. This research discussed Misbah Musthofa's perspective of religious tolerance by using prophetic social science analysis. There are two important points that can be deduced from his thoughts regarding tolerance. First, people of other religions must be treated well and fairly as long as they are not bad to us. Second, this attitude of tolerance must be accompanied by the belief that Islam is the only true religion (positive pluralism). In general, his thoughts regarding religious tolerance are very much in line with the pillars of humanization, liberation and transcendence in prophetic social sciences and are sufficiently capable of eradicating bad stigma against Islam.